Pengaruh Kepemimpinan Autentik terhadap Kinerja Guru SMP Man Ana Kecamatan Pamijahan Bogor - Zainal Abidin; Edi Abdul Latif (Reslaj : Religion Education Social Laa Roiba Journal, 2021)
Teacher performance is the success of teachers in implementing quality teaching and learning activities, including loyalty and high commitment to teaching tasks, mastering and developing methods, mastering learning materials and using learning resources, being responsible for monitoring teaching and learning outcomes, teaching discipline and other tasks. , creativity in implementing teaching, interacting with students to generate motivation, good personality, honesty and objectivity in guiding students, able to think systematically about what they do, and understanding in teaching administration. This research was conducted at SMP Man Ana, Pamijahan District, Bogor Regency. This study aims to determine the effect of authentic leadership on teacher performance at SMP Man Ana, Pamijahan District, Bogor. This study uses quantitative methods with data collection techniques using a questionnaire or questionnaire. The sample used was 20 teachers. The sampling method used in this study is the saturated sample method. The data analysis technique used is simple linear regression. Based on the results of the analysis, it was found that authentic leadership has a positive effect on teacher performance. This shows that the stronger the effect of authentic leadership by the principal, the higher the performance produced by the teacher. Therefore, to improve teacher performance, it is expected that there will be an increase in the authentic leadership indicators of school principals.